Flexitibia, a new genus of Harpactorinae (Hemiptera: Heteroptera: Reduviidae), with a discussion on the functional morphology of fore legs of the related genera - Zhao, Ping; Pham, Minhlan; Truong, Xuan Lam; Cai, Wanzhi (Zootaxa, 2014)
Flexitibia, a new genus, in the division Euagorasaria of the assassin bug subfamily Harpactorinae from Yunnan Province of China is described. The type species, Flexitibia orientalis sp. nov., is described and illustrated. A key to the closely related genera is provided. The type specimens are kept in the Entomological Museum of China Agricultural University, Beijing.